Technology of Making Pectin from Flaxseed - Bozorova S. T.; Jumanova M; Inoyatova X. (Indonesian Journal of Innovation Studies, 2019)
This paper investigates major points of the technology of making pectin from flaxseed. Case of the study makes both methodological and theoretical points. It concludes, major features of the research for the further investigations